Low- and Middle-Income Regions Will Struggle to Reach Target for Reducing Stroke - Kuznar, Wayne (MD Conference Express, 2015)
Achieving the WHO global target of a 25% reduction in the rate of premature mortality from stroke and other NCDs by 2025 will require aggressive risk factor reduction. Intense regional-specific strategies will be required, as the risk factor burden varies widely by region.